Analysis of the Effect of Adding a Water Heater to the R290 Split Air Conditioning Instead of R22 - Widodo; Nulhakim, Lukman; Syafrizal; Tauvana, Ade Irvan; Kurnia, Deva Arya; Asmoro, Purwandito Tulus (Program Studi Teknik Mesin Universitas Pamulang, 2025)
The heat generated by split air conditioning (AC-Split) is sufficiently high to be utilized as a heat exchanger. The installation of a heat exchanger device, referred to as an Air Conditioning Water Heater (ACWH), is used to heat water in a tank by utilizing the waste heat from the condenser. In this study, refrigerant R290 will be used as a replacement for R22, with the aim of eliminating the Ozone Depleting Potential (ODP) and Global Warming Potential (GWP) associated with R22. Calculations are carried out to ensure the performance of the split AC by testing each refrigerant, R22 and R290, installed in the heat exchanger system. The test data is calculated and analyzed based on the performance on the vapor compression diagram. The results of the performance calculations of each R290/R22 refrigerant COP: 9.7/6.4, compression work: 28.7/25.72 kJ/kg, cooling effect, and electrical power: 881/976 Watts. The calculation results of R290 have better performance compared to R22, especially in electrical power. R290 is 10% lower than R22, COP is 34% higher, and it is ODP and GWP-free.